Regulatory challenges and prospect of Islamic Banks in Turkey and Indonesia: propose for sustainability. - Zulfahmi; Luthfi Rantaprasaja (Journal of Islamic, Social, Economics and Development, 2025)
The issues and challenges faced by Islamic banking in Indonesia and Turkey are similar and appropriate to explore. Despite having a legacy of strong Islamic law, the majority Muslim population, and the strategic location of each country, they have not been able to dominate the local market share of Islamic banks compared with conventional banks. This research aims to examine Islamic banks in terms of the distinguish regarding to the legal and regulatory progress in both countries, especially on their SWOT and propose strategies for developing and sustainability. This study is a qualitative study as the main method that takes data from various works of literature, namely books, journals, and other sources. Primary data has also been explored by conducting an in-depth interview with the experts regarding these issues. The expert interview has been conducted in Indonesia, and Turkey from 2019 to 2022. Basically, they were Bankers, Islamic Scholars, Regulators, and Academicians. Meanwhile, this research also applied a comparative approach. This research found that government support stands as the first priority from an opportunity aspect. Islamic bank in those countries also needs to be aware of the absence of separate law as the main priority of threats aspect. Another finding shows that separate law and regulation is the main strategy to enhance Islamic banks in each country. This study could serve as a reference point for the regulator in formulating appropriate policy strategies to increase the market share of Islamic banks in Malaysia, Indonesia, and Turkey. This research is also expected to be able to contribute to enriching scientific studies in an effort to popularize Islamic banking in whole Muslim countries.